Prevalence and mortality among children with anorectal malformation: A multi-country analysis - Kancherla, Vijaya (2023)
Purpose: We examined the total prevalence, trends in prevalence, and age-specific mortality among individuals with anorectal malformation (ARM). Methods: We conducted a retrospective cohort study using data from 24 population- and hospital-based birth defects surveillance programs affiliated with the International Clearinghouse for Birth Defects Surveillance and Research (ICBDSR) from 18 countries and for births from 1974 to 2014. We estimated pooled and program-specific total prevalence per 10,000 total births. Poisson regression was used to assess time trends in prevalence from 2001 to 2012 when most programs contributed data. We calculated selected age-specific proportions of deaths, stratified by case status. Results: The pooled total prevalence of ARM was 3.26 per 10,000 total births (95% Confidence Interval = 3.19, 3.32) for birth years 1974–2014. About 60% of cases were multiple or syndromic. Prevalence of multiple, syndromic, and stillborn cases decreased from 2001 to 2012. The first week mortality proportion was 12.5%, 3.2%, 28.3%, and 18.2% among all, isolated, multiple, and syndromic cases, respectively. Conclusions: ARM is relatively rare, with multiple and syndromic cases showing decreasing prevalence during the study period. Mortality is a concern during the first week of life, and especially among multiple and syndromic cases. Our descriptive epidemiological findings increase our understanding of geographic variation in the prevalence of ARM and can be used to plan needed clinical services. Exploring factors influencing prevalence and mortality among individuals with ARM could inform future studies.